Driving forces for changes in geographical distribution of Ixodes ricinus ticks in Europe - Medlock, Jolyon M; Hansford, Kayleigh M; Bormane, Antra; Derdakova, Marketa; Estrada-Peña, Agustín; George, Jean-Claude; Golovljova, Irina; Jaenson, Thomas G T; Jensen, Jens-Kjeld; Jensen, Per M; Kazimirova, Maria; Oteo, José A; et al. (Parasites & vectors, 2013)
Many factors are involved in determining the latitudinal and altitudinal spread of the important tick vector Ixodes ricinus (Acari: Ixodidae) in Europe, as well as in changes in the distribution within its prior endemic zones. This paper builds on published literature and unpublished expert opinion from the VBORNET network with the aim of reviewing the evidence for these changes in Europe and discusses the many climatic, ecological, landscape and anthropogenic drivers. These can be divided into those directly related to climatic change, contributing to an expansion in the tick’s geographic range at extremes of altitude in central Europe, and at extremes of latitude in Scandinavia; those related to changes in the distribution of tick hosts, particularly roe deer and other cervids; other ecological changes such as habitat connectivity and changes in land management; and finally, anthropogenically induced changes. These factors are strongly interlinked and often not well quantified. Although a change in climate plays an important role in certain geographic regions, for much of Europe it is non-climatic factors that are becoming increasingly important. How we manage habitats on a landscape scale, and the changes in the distribution and abundance of tick hosts are important considerations during our assessment and management of the public health risks associated with ticks and tick-borne disease issues in 21 st century Europe. Better understanding and mapping of the spread of I. ricinus (and changes in its abundance) is, however, essential to assess the risk of the spread of infections transmitted by this vector species. Enhanced tick surveillance with harmonized approaches for comparison of data enabling the follow-up of trends at EU level will improve the messages on risk related to tick-borne diseases to policy makers, other stake holders and to the general public.